Improving Professional Teacher Competence through Learning Supervision for Madrasah Teachers with a Background in Islamic Boarding School Education - Muslam (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2024)
This research discussed learning supervision for madrasah teachers who had an educational background in Islamic boarding schools to improve the professional competence of teachers. The objectives of this study were to find out the condition, the professional competence, and the implementation of learning supervision for teachers with an educational background in Islamic boarding schools (Pesantren) at MTs. Ma'arif NU Semarang , Indonesia. This qualitative research field used observation, interview, and documentation methods. Data analysis in this study used qualitative analysis with the stages of data reduction, data presentation (data display), and data verification (conclusion drawing). The results and findings of the research were the educational backgrounds of Pesantren with the culture of Santri, they brought from their respective Pesantren with various disadvantages and advantages. It was found that there were teachers who were rebellious and tended not to follow the rules and demands. There were eccentric teachers, laziness, and others. Moreover, they also had advantages in the deep understanding of religious lessons. Teachers of MTs Ma'arif NU Semarang City with an educational background in Pesantren obtained three categories: the good category of 15.38%, sufficient 7.69%, and low 76.92%. Thus, efforts needed to be made to improve the professional competence of these teachers.